2020
DOI: 10.26694/2238-7234.9111-19
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of hypertensive patients accompanied by a family health strategy team / Qualidade de vida de hipertensos acompanhados por uma equipe da estratégia saúde da família / Calidad de vida de hipertensos acompañados por un equipo..

Abstract: Objetivo: Avaliar a qualidade de vida de pacientes hipertensos acompanhados por uma equipe da Estratégia Saúde da Família. Metodologia: Estudo descritivo, quantitativo realizado com 150 hipertensos de uma Unidade Básica de Saúde de Caxias-MA. Utilizou-se dois instrumentos: um questionário estruturado e o instrumento Medical Outcomes Study 36 - Item Short - Form Health Survey (SF-36) de qualidade de vida. Os dados obtidos, foram analisados no software Statistical Package for the Social Sciences. O estudo foi ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Its rate can exceed 80% in adult subpopulations (Rudulfo, 2019;WHO, 2019). Although there is evidence about the benefits of physical activity for the quality of life of individuals with arterial hypertension, studies have identified high levels of sedentary lifestyle in this population (Abreu et al, 2020;Martins et al, 2015;Oliveira et al, 2019). Additionally, "Activity intolerance" associated with cardiovascular compromise was responsible for a 76% increase in the chance of having SL.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Its rate can exceed 80% in adult subpopulations (Rudulfo, 2019;WHO, 2019). Although there is evidence about the benefits of physical activity for the quality of life of individuals with arterial hypertension, studies have identified high levels of sedentary lifestyle in this population (Abreu et al, 2020;Martins et al, 2015;Oliveira et al, 2019). Additionally, "Activity intolerance" associated with cardiovascular compromise was responsible for a 76% increase in the chance of having SL.…”
Section: Backg Rou N Dmentioning
confidence: 99%